1950
DOI: 10.1152/ajplegacy.1950.161.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chemical Studies in Skeletal Muscle Following Neurotomy and Tenotomy

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1952
1952
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It was demonstrated that the membrane resting potentials of denervated muscle fibres tended to oscillate. The instability of membrane potential, which was not observed in innervated muscle fibres, may indicate metabolic changes in denervated muscles, as evidenced by the studies of Humoller, Griswold & McIntyre (1950) and Humoller, Hatch & McIntyre (1951).…”
Section: Discussionmentioning
confidence: 90%
“…It was demonstrated that the membrane resting potentials of denervated muscle fibres tended to oscillate. The instability of membrane potential, which was not observed in innervated muscle fibres, may indicate metabolic changes in denervated muscles, as evidenced by the studies of Humoller, Griswold & McIntyre (1950) and Humoller, Hatch & McIntyre (1951).…”
Section: Discussionmentioning
confidence: 90%
“…These data suggest that the level of spontaneous fibrillation activity is related to muscle metabolic rate; however, (as has been noted by numerous authors) it is often difficult to determine which changes contribute to development of fibrillation and which are a consequence of it. Indeed, denervated muscle exhibits decreased levels of glycogen 83-85 and changes in activity levels of numerous enzymes (e.g., decreased succinic dehydrogenase 86 and cytochrome oxidase activities 87 with increased hexokinase activity 88 ) and other factors involved in carbohydrate metabolism. 83 , 84 , 86 , 88 In 1950, Humoller and co-workers compared metabolic parameters in denervated and tenotomized muscle and found that glycogen levels dropped in both sets of samples and that in the tenotomized muscles this decline started before the commencement of the fibrillation they detected, suggesting that decreased glycogen levels may contribute to production of the spontaneous activity.…”
Section: Origins and Consequences Of Muscle Fibrillationmentioning
confidence: 99%
“…Intracellular potassium is lost under anaerobic conditions from nerve (Shanes, 1951), from denervated ganglia (Gertner & Reinert, unpublished observations) and from denervated muscle (Humoller, Griswold & McIntyre, 1950a). In denervated muscle there is inhibition of glycogen synthesis and decrease of the resting potential (Ware, Bennett & McIntyre, 1954), reduction of phosphorylation (Varga, Kostya, Szabo, Aszodi & Kesztyiis, 1950) and decrease of ATP and creatine phosphate (Levine, Hechter & Soskin, 1941;Humoller, Griswold & McIntyre, 1950b).…”
Section: Metabolism Of Gangliamentioning
confidence: 99%